2001
DOI: 10.1074/jbc.m103023200
|View full text |Cite
|
Sign up to set email alerts
|

A New Pathway for Glucose-dependent Insulinotropic Polypeptide (GIP) Receptor Signaling

Abstract: The hormone glucose-dependent insulinotropic polypeptide (GIP) is an important regulator of insulin secretion. GIP has been shown to increase adenylyl cyclase activity, elevate intracellular Ca 2؉ levels, and stimulate a mitogen-activated protein kinase pathway in the pancreatic ␤-cell. In the current study we demonstrate a role for arachidonic acid in GIP-mediated signal transduction. Static incubations revealed that both GIP (100 nM) and ATP (5 M) significantly increased [ 3 H]AA release. Our data suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Analogues resulting from the connection of (1-14) and (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) domains by one or two Ahx residues (analogues 13 and 14, respectively) showed noticeable increases in cAMP production with EC 50 values in the low micromolar range, similar to analogues 4 and 6 (Table 2, Figure 2A). The introduction of an extra Ahx residue (analogue 15) resulted in nearly complete loss of ability to stimulate cAMP production, perhaps because of excessive conformational freedom induced by three successive aminohexanoic acids ( Figure 2A).…”
Section: Resultsmentioning
confidence: 51%
“…Analogues resulting from the connection of (1-14) and (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) domains by one or two Ahx residues (analogues 13 and 14, respectively) showed noticeable increases in cAMP production with EC 50 values in the low micromolar range, similar to analogues 4 and 6 (Table 2, Figure 2A). The introduction of an extra Ahx residue (analogue 15) resulted in nearly complete loss of ability to stimulate cAMP production, perhaps because of excessive conformational freedom induced by three successive aminohexanoic acids ( Figure 2A).…”
Section: Resultsmentioning
confidence: 51%
“…An intervening peptide (C terminus of ␤-adrenergic receptor kinase) that we previously employed to investigate GIP signaling (38) was expressed in increasing amounts in rGIP-15 cells, but it was unable to reverse 1 nM GIP-mediated activation of ERK1/2 phosphorylation (Fig. 8), thus providing evidence against a role for G␤␥ signaling in ERK1/2 regulation.…”
Section: Gip Activates Erk Via Rap1 Independently Of G␤␥ and Src-mentioning
confidence: 97%
“…Supportive studies with a third ␤-cell line, Brin-D11, also mimic these actions of GIP (data not shown). GIP signals via cAMP and arachidonic acid (AA) in rGIP-15 cells and ␤-cell lines (5,38). To identify the proximal regulator of the ERK module, we tested the ability of these two second messengers to modulate ERK1/2 phosphorylation, while using the phorbol ester, phorbol myristic acid (PMA), as a positive control for ERK1/2 activation (Fig.…”
Section: and Ins-1 (832/13) Ranked As Highly Expressedmentioning
confidence: 99%
“…In GC cells, sst 2 receptors that are coupled to [Ca 2+ ] i control, modulate cAMP pathways, whereas sst 1 receptors are coupled to phospholipase A 2 pathways independently of [Ca 2+ ] i control [15]. Since the phospholipase A 2 pathway is involved in secretory events in different experimental models [37, 38, 39], it is tempting to speculate that the inhibition of this pathway may be also responsible for the sst 1 control of GH secretion in GC cells.…”
Section: Discussionmentioning
confidence: 99%